Developing and validating a wisdom scale inventory (WISI) from an islamic perspective based on Ibn Qayyim's classification of wisdom - Ali, Ibrahim (2015)
The purpose of this study was to develop an instrument called Wisdom Scale Inventory (WISI) for measuring wisdom from an Islamic perspective based on Ibn Qayyim al-Jawziyyah's classification of wisdom and to validate its psychometric properties. The samples of the study were heterogeneous comprising of 700 postgraduate master and PhD students who were randomly sampled from five outstanding public Universities in Malaysia namely, International Islamic University Malaysia (IIUM), University of Malaya (UM), Universiti Putra Malaysia (UPM), Universiti Teknologi Mara (UiTM), and the Universiti Sains Islam Malaysia (USIM). The instrument developed is a wisdom model that composed of two scales namely, knowledge ('ilm) and action ('amal). The knowledge scale has two subscales namely, understanding (fahm) and realization (idrāk) while the action scale consisted of two subscales namely; inner action ('amal bātin) and outer action ('amal ẓāhir). The instrument has 46 items and was empirically tested using several methods of reliabilities and validities. Principal Component Analysis (PCA) and Confirmatory Factor Analysis (CFA) were utilized to analyse the data collected. SPSS version 18 was used to analyse the data for PCA while AMOS version 16 was employed to analyse the data for CFA. Based on the analysis, the results of the study provided evidence that the devised instrument achieved sound psychometric properties. The results of the reliability test indicated that the developed instrument was reliable yielding the Cronbach's Alpha of 0.863. The PCA generated four- factor solution which accounted for 60.9% approximately of the total variance. The findings of CFA revealed the revised model overall goodness-of-fit-statistics at RMSEA = .039, GFI = .976, TLI = .964, CFI = .972, the chi-squared statistics (2 /df) = 2.062, p = .00 showing that the model statistically fits the data. This confirms understanding, realisation, inner and outer actions as a measure of wisdom in accordance with the theory of Ibn Qayyim. The results of the invariance analysis showed that the samples are not statistically significantly different across gender and age in terms of wisdom. Thus, the results of analyses suggest that wisdom is a valid and reliable measure and WISI could be used in the Humanities and Revealed Sciences.